2018
DOI: 10.1002/pmic.201700465
|View full text |Cite
|
Sign up to set email alerts
|

Immunopeptidomic Profiling of HLA‐A2‐Positive Triple Negative Breast Cancer Identifies Potential Immunotherapy Target Antigens

Abstract: The recent development in immune checkpoint inhibitors and chimeric antigen receptor (CAR) T‐cells in the treatment of cancer has not only demonstrated the potency of utilizing T‐cell reactivity for cancer therapy, but has also highlighted the need for developing new approaches to discover targets suitable for such novel therapeutics. Here we analyzed the immunopeptidomes of six HLA‐A2‐positive triple negative breast cancer (TNBC) samples by nano‐ultra performance liquid chromatography tandem mass spectrometry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 46 publications
2
32
0
Order By: Relevance
“…IL-32 increased migration and invasion capacities of TNBC cells [64] and promoted TNBC cell growth [65]. In addition, IL-32 is a potential immunotherapy target antigen in HLA-A2-positive TNBC [66]. Based on these results, a high level of IL32 in TNBC (Figure 2) may be involved in aggressiveness of TNBC despite unclear direct relationship between SAA and IL32.…”
Section: Discussionmentioning
confidence: 99%
“…IL-32 increased migration and invasion capacities of TNBC cells [64] and promoted TNBC cell growth [65]. In addition, IL-32 is a potential immunotherapy target antigen in HLA-A2-positive TNBC [66]. Based on these results, a high level of IL32 in TNBC (Figure 2) may be involved in aggressiveness of TNBC despite unclear direct relationship between SAA and IL32.…”
Section: Discussionmentioning
confidence: 99%
“…Improvements in sensitivity and speed of this instrumentation now make peptidome profiling of HLA-bound peptides relatively routine and have opened up the possibility to work with limited patient-derived material ( 90 , 91 ). Such analysis also allows for unambiguous definition of posttranslational modifications of epitopes ( 92 95 ) or from proteome extracts ( 19 , 96 98 ) of patient-derived material. To date, characterization of the HLA class I–bound peptides from human β-cells has been limited, primarily due to difficulties in obtaining sufficient material ( 20 ).…”
Section: Novel Technologies In T-cell Response and Autoantigen Identimentioning
confidence: 99%
“…This was the first report showing that IL-32β plays a role in the regulation of breast cancer cell metabolism. A recent report suggested that IL-32 is a prospective therapeutic target for triple negative breast cancer, since IL-32 was more highly expressed in cancer tissue from patients with triple negative breast cancer (53), implying a critical role of IL-32 in the progression of the breast cancer.…”
Section: Role Of Il-32 In Other Types Of Cancermentioning
confidence: 99%